Aesthetic Breast Surgery Under Cold Tumescent Anesthesia: Feasibility and Safety in Outpatient Clinic. Issue 4 (October 2019) - Ceccarino, Raffaele; Di Micco, Rosa; Cappelletti, Renato
Abstract : Abstract: Throughout the last decade, aesthetic breast surgery has enormously spread in the outpatient clinic setting where plastic surgeons perform the vast majority of procedures under local anesthesia as day-case operations. The "tumescent anesthesia" is defined as the injection of a dilute solution of local anesthetic combined with epinephrine and sodium bicarbonate into subcutaneous tissue until it becomes firm and tense, which is "tumescent." The "cold tumescent anesthesia" (CTA) derives from Klein's solution with the introduction of a new concept, which is the low temperature (4°C) of the injected solution. This novelty adds further anesthetic and hemostatic power to the well-known benefits of tumescent anesthesia. The authors report their experience with CTA in the last 15 years in the setting of aesthetic breast surgery, describing in detail the anesthesia protocol, surgical outcomes, and patient satisfaction. A total of 1541 patients were operated on during the study period and were included in this retrospective analysis. The types of breast procedures were breast augmentation in 762 cases (49.4%), mastopexy with implants in 123 patients (8.0%), mastopexy without implants in 452 cases (29.3%), and breast reduction in 204 cases (13.3%). Patient mean age was 42.8 years (range, 18–67 years). The mean operating time was 37 ± 32 minutes for breast augmentation, 78 ± 24 minutes for mastopexy with implants, 58 ± 18 minutes for mastopexy without implants, and 95 ± 19 minutes for breast reduction. No major complications occurred, and no conversion to general anesthesia was required. The median recovery time was 150 minutes (range, 120–210 minutes), and all patients were discharged within 3 hours after surgery. Wound or implant infections occurred in 33 patients (2.1%), wound dehiscences in 21 (1.4%), and postoperative bleeding requiring return to theater in 2 cases (0.1%). Thirteen patients (0.8%) developed capsular contracture. Fifteen patients (1%) required reintervention due to implant rotation or rupture. The median visual analog scale score was 1.8 (interquartile range, 1–3) after discharge. Patient satisfaction was very high in 91.3% (n = 1407) of the cases. In experienced hands, CTA can shorten operating time with high patient satisfaction and a low complication rate. These preliminary data could be hypothesis generating for future multicenter prospective trials done to confirm the benefits of CTA in other surgical fields. Abstract : Supplemental digital content is available in the text.